Enhancing DevOps Risk Assessment with Cross-Domain Knowledge - Phani Monogya Katikireddi (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The report proposes to improve the risk assessment of DevOps procedures through cross-referencing knowledge. It focuses on cybersecurity, artificial intelligence, and project management. It shows how cross-cutting strategies successfully manage the risks and enhance CI/CD processes. Based on the report, this paper also presents a simulation of the cross-domain strategies, the real-time scenarios illustrating the application of the techniques, the impacts, and real-life cases showing the challenges arising when applying the cross-domain strategies. Possible solutions to these challenges, such as cross-training and automation, are also highlighted. It is concluded that drawing on multiple perspectives enables an organization to redesign its risk management, making it more adaptable, robust, and resource-effective.
Keywords: DevOps; Risk Assessment; Cross-Domain Knowledge; Continuous Integration/Continuous Deployment; Simulation; Automation; Risk Mitigation